Multiauthority Attribute-Based Encryption with Traceable and Dynamic Policy Updating. (26th February 2021) - Ling, Jie; Chen, Junwei; Chen, Jiahui; Gan, Wensheng
Abstract : Ciphertext policy attribute-based encryption (CP-ABE) is an encryption mechanism that can provide fine-grained access control and adequate cloud storage security for Internet of Things (IoTs). In this field, the original CP-ABE scheme usually has only a single trusted authority, which will become a bottleneck in IoTs. In addition, different users may illegally share their private keys to obtain improper benefits. Besides, the data owners also require the flexibility to change their access policy. In this paper, we construct a multiauthority CP-ABE scheme on prime order groups over a large attribute universe. Our scheme can support white-box traceability along with policy updates to solve the abovementioned three problems and, thus, can fix the potential requirements of IoTs. More precisely, the proposed scheme supports multiple authority, white box traceability, large attribute domains, access policy updates, and high expressiveness. We prove that our designed scheme is static secure and traceable secure based on the state-of-the-art security models. Moreover, by theoretical comparison, our scheme has better performance than other schemes. Finally, extensive experimental comparisons show that our proposed algorithm can be better than the baseline algorithms.